Relevansi konsep epistemologi Islam dengan pendidikan pesantren - Ulfatun Naili Nadhiroh; Nur Hasan (At Turots: Jurnal Pendidikan Islam, 2021)
Epistemology is an activity that is closely related to a cognitive act in the cultural process, namely the acquisition of knowledge (al-iktisabu al-ma'rifat) and the production of knowledge (intaj al-ma'rifat). And the important instrument used is the al-mukawwin sense, a cultural reasoning device (the set of reasoning and behavior that results from that device) used to find out and produce knowledge. And that knowledge is constructed in systems of thinking and values. According to Abid al-Jabiri, this experience is useful for studying and identifying the knowledge that develops in the world of education, including Islamic education in Islamic boarding schools. This research uses the library research method. And it results that Al-Jabiri's epistemology has relevance to Islamic education in Islamic boarding schools, for the following reasons; first, education is the theological articulation of norms and values ​​in an interactive, instrumental and institutionalized socio-cultural dialect; second, education includes reasoning and the application of norms and values ​​that take place in people's lives; third, For this to happen, a system of values ​​and thinking is needed which is called an epistemic system to produce and acquire knowledge. And these tools are human capital to interact with the main sources of Islam, be it naqliyah texts (Al-Qur'an Hadith) or aqliyah texts (Ijma', Qiyas, and others).